MANAGEMENT FISIOTERAPI PADA CARPAL TUNNEL SYNDROME: A CASE REPORT - Ayu Tri Kusumaningrum Subiyanto; Umi Budi Rahayu; Katno Asha (Ahmar Metastasis Health Journal, 2023)
Carpal Tunnel Syndrome is a peripheral neuropathy in which there is increased pressure around the median nerve which causes various symptoms such as tingling, wrist pain, paresthesia, and a burning sensation in the hands. Various factors have been speculated to contribute to the occurrence of CTS, including hereditary neuropathy, trauma to the forearm, repetitive motion work on the wrist, inflammation of the tendons, metabolic and endocrine diseases, malignancy to degenerative diseases. To reduce pain when the patient is at home, physiotherapists provide independent exercises that can be done at home with modified myofascial stretching. Kinesio tapping is an adjunctive treatment method that is suggested to be effective in regulating normal tissue function and supporting wound healing mechanisms. It has been found to be effective in muscle problems for pain relief by reducing pressure on pain receptors and supporting and protecting muscle tissue. Kinesio tapping is also known to be effective in the conservative treatment of CTS either alone or in combination with other therapeutic agents. To determine the effect of exercise therapy and kinesio tapping given to CTS patients. This study uses a case study. measurement of pain using the Numeric Rating Scale (NRS), measurement of muscle strength using Manual Muscle Testing (MMT), Goniometer to measure the Range of Joint Motion (ROM), Evaluation of Functional Ability with the Buston Questionaire Carpal Tunnel Syndrome (BQCTS) is a measuring tool to measure functional ability in CTS. After 3 physiotherapy interventions, results were obtained which showed a decrease in pain. Silent pain from 1 to 0, tenderness from 5 to 2, and motion pain from 6 to 2. For muscle strength, there was an increase in the wrist flexor muscle group from 3+ to 4. For the range of motion of the joints, there was no significant increase due to the time of intervention very limited. As well as found an increase in functional activity and a decrease in the degree of pain. Exercise therapy and Kinesio Taping are effective for reducing pain, increasing muscle strength, and increasing range of motion resulting in increased functional ability.